Acute eosinophilic pneumonia caused by camostat mesilate: The first case report. (2016) - Ota, Shinichiro; Hara, Yu; Kanoh, Soichiro; Shinoda, Masahiro; Kawano, Shuichi; Fujikura, Yuji; Kawana, Akihiko; Shinkai, Masaharu
Abstract: Camostat mesilate is in widespread clinical use mainly to treat chronic pancreatitis, and drug-induced lung injury has not been previously reported. However, pulmonary infiltration with peripheral blood eosinophilia appeared after taking camostat mesilate for ten days. The histological findings showed eosinophilic infiltration into the alveolar space and interstitum, and drug lymphocyte stimulation test of peripheral blood was positive. Both peripheral blood eosinophilia and pulmonary involvements improved two weeks later with the cessation of this drug. To the best of our knowledge, this case is the first report of camostat mesilate-induced acute eosinophilic pneumonia.